(MD) Associate Professor; Department of Forensic Medicine, J.N Medical College Aligarh Muslim University Aligarh. (U.P) India - Patel, Dixit S; Vaghela, Alpesh C; Shaikh, M M; Prajapati, Pankaj; Shah, Kalpesh (Journal of Forensic Medicine and Toxicology, 2017)
Medico legal autopsies are conducted in all cases of unnatural deaths and unidentified bodies. The case load of unidentified bodies in autopsy at Ahmedabad is astounding. Opinion about the cause of death in unknown dead bodies is a test of ability of the Forensic expert and on many occasions yields little or no results1. The reasons may be inadequate/no history, disinterested Investigating officers unwilling to properly work out the case, partial/ complete decomposition/destruction/mutilation of the body, etc. A total of 4137 dead bodies were brought for postmortem examination to the Mortuary Complex of Civil Hospital, Ahmedabad during JANUARY 2014 to DECEMBER 2014 .Out of them 312 (7.54%) dead bodies were unknown at the time of autopsy.Majority of cases were above 60 years age group, 31.73%. Majority of the opinions regarding the cause of death were given as coronary artery disease, 20.19%, followed by “no definite opinion”, 19.22%. Viscera for chemical analysis were sent in 44.23%, histopathology in 17.30% and for microbiology in 7.69% cases.
Keywords: Unidentified bodies; death; cause of death